ANALISIS PENGARUH BATU KAPUR TERHADAP PENURUNAN KADAR SULFUR DIOKSIDA GAS BUANG BOILER PADA PT. PLN (PERSERO) UNIT PLTU BARRU - Abdul Rahman; Werni Gusti Marampa (Jurnal Teknik Mesin Sinergi, 2017)
In line with the development of coal utilization in Indonesia, there are also some obstacles that hinder the development. The main obstacle is the presence of SO2 gas of coal combustion products which can cause air pollution. To reduce SO2 gas can be done by reducing the sulfur content of the coal burned before (desulfurization), with the aim to determine the effect of limestone to decreased levels of sulfur and sulfur removal efficiency resulting in an environmentally friendly exhaust gas in accordance with the regulations of Ministry of Environment (MoE) . This research was conducted by using the method of direct observation on the components of the power plant which will review the boiler, chimney and CEMS as well as interviews with relevant parties about the desulfurization process. The results of the study indicate that the use of limestone to reduce levels of sulfur is an effective option for every plant where the efficiency of desulfurization process reaches 98%.